2002
DOI: 10.1093/toxsci/65.1.52
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamo-Pituitary-Thyroid (HPT) Axis: A Target of Nonpersistent ortho-Substituted PCB Congeners

Abstract: Coplanar polychlorinated biphenyls (PCBs) cause adverse effects in developing and adult animals. Less is known about the effects of nonplanar ortho-substituted PCBs. We investigated the effects of 2 nonplanar PCB congeners, 95 (2,3,6-2',5'-penta CB) or 101 (2,4,5-2',5'-penta CB), and estradiol on selected endocrine parameters. In Study 1, weanling female Sprague-Dawley (S-D) rats were given a single dose of PCB 95 ip at 4, 8, 16, and 32 mg/kg/day for 2 consecutive days and killed 24 h after the last dose. PCB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 39 publications
2
32
1
Order By: Relevance
“…Taking into account that thyroid hormones play an important role in the growth and differentiation of almost every tissue in the body, and are major regulators of energy metabolism and mitochondrial functioning (McNabb, 1995(McNabb, , 2007, disruption of the HPT axis may cause deleterious effects in several peripheral tissues and organs. Numerous studies have demonstrated that TCDD and PCBs change thyroxine (T 4 ) and triiodothyronine (T 3 ) concentrations in the blood of rodents (Craft et al, 2002;Desaulniers et al, 1999;Khan et al, 2002) and humans (Nagayama et al, 1998;Schell et al, 2004). Three possible ways of this particular disruption have been proposed: (1) direct inhibition of the pituitary or thyroid gland (Webb and McNabb, 2008), (2) displacement of T 4 from thyroid hormone binding proteins and the consequent release of free T 4 , resulting in enhanced metabolism and excretion (Chauhan et al, 2000;Pearce and Braverman, 2009), (3) induction of hepatic uridine diphosphate glucuronosyl-transferases (UDPGTs) activity mediated by AhR, and subsequent enhanced exertion of T 4 -glucuronide in bile (Hood et al, 2003;Kato et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that thyroid hormones play an important role in the growth and differentiation of almost every tissue in the body, and are major regulators of energy metabolism and mitochondrial functioning (McNabb, 1995(McNabb, , 2007, disruption of the HPT axis may cause deleterious effects in several peripheral tissues and organs. Numerous studies have demonstrated that TCDD and PCBs change thyroxine (T 4 ) and triiodothyronine (T 3 ) concentrations in the blood of rodents (Craft et al, 2002;Desaulniers et al, 1999;Khan et al, 2002) and humans (Nagayama et al, 1998;Schell et al, 2004). Three possible ways of this particular disruption have been proposed: (1) direct inhibition of the pituitary or thyroid gland (Webb and McNabb, 2008), (2) displacement of T 4 from thyroid hormone binding proteins and the consequent release of free T 4 , resulting in enhanced metabolism and excretion (Chauhan et al, 2000;Pearce and Braverman, 2009), (3) induction of hepatic uridine diphosphate glucuronosyl-transferases (UDPGTs) activity mediated by AhR, and subsequent enhanced exertion of T 4 -glucuronide in bile (Hood et al, 2003;Kato et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lyche et al (2004) observed no significant effect on PRL levels of female goat prenatally exposed to low doses of CB-126 and CB-153 (similar to environmental doses) [19]. However, acute exposure to non persistent non coplanar congeners leads to transitory rise of blood PRL levels and to decrease of hypothalamic dopamine levels in developing rats [20]. In adult man, high dietary exposure to PCB and pesticides, from fish consumption, was not linked to circulating levels of PRL [21].…”
Section: Relation Of Cord Blood Pcb To Prlmentioning
confidence: 89%
“…Furthermore, there is substantial evidence that perinatal exposure to PCBs and their hydroxylated metabolites decreases the concentrations of THs in the offspring (Crofton et al 2000a,b, Meerts et al 2002, Boas et al 2012. Exposure to PCBs induces hypothyroidism (decreases the concentrations of THs and increases those of TSH) in rats (Khan et al 2002, Powers et al 2006, sledge dogs (Kirkegaard et al 2011), monkeys (Boas et al 2006), and children living near PCB-contaminated sites (Schell et al 2004). Additionally, the elevation in DNA fragmentation reported herein is consistent with results of previous laboratory experiments showing that PCBs have the ability to break DNA strands (Ahlborg et al 1992), where they may directly act on the thyroid receptor (TR) to modulate its action or indirectly act on an unknown TRbinding protein, which may then lead to conformational changes in the TR-DNA-binding domain to dissociate TR from the T 3 -responsive element (TRE; Miyazaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The pups were given a single dose of PCB 95 (SigmaAldrich; 32 mg/kg per day, by i.p. injection) (Khan et al 2002) for 2 consecutive days and killed 24 and 48 h after the administration of the last dose. At PNDs 17 and 18, the newborns were subsequently killed under mild diethyl ether anesthesia, and blood samples were collected and centrifuged at 1006.2 g for 30 min.…”
Section: Animals and Treatmentsmentioning
confidence: 99%